2017
DOI: 10.1055/s-0037-1602592
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making in Interventional Oncology: Ablative Options in the Lung

Abstract: Image-guided ablation is safe and effective for the treatment of both primary and metastatic tumors in the lung. This article reviews the three most commonly used ablative options: radiofrequency ablation, microwave ablation, and cryoablation. We describe the advantages of each ablation modality in the lung and how to choose the most appropriate ablation device based on patient and tumor characteristics. The optimal technique for lung ablation is discussed and technical tips for improving clinical outcome are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Therefore, as with MWA, a tangential approach to peripheral lesions with a long path through normal lung is recommended. 12 Cryoablation generates a considerable amount of alveolar hemorrhage during thaw cycles. This lung opacification is generally greater with cryoablation than with heat-based modalities and can result in intraprocedural bronchial obstruction and postprocedural hemoptysis and hypoxia.…”
Section: Safetymentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, as with MWA, a tangential approach to peripheral lesions with a long path through normal lung is recommended. 12 Cryoablation generates a considerable amount of alveolar hemorrhage during thaw cycles. This lung opacification is generally greater with cryoablation than with heat-based modalities and can result in intraprocedural bronchial obstruction and postprocedural hemoptysis and hypoxia.…”
Section: Safetymentioning
confidence: 99%
“…8,9 IGTA has several advantages over surgery and SBRT in the treatment of lung metastases, including repeatability and sparing of normal lung parenchyma. [10][11][12] Multiple studies have shown that patients undergoing local therapy for oligometastatic disease are likely to develop new foci of lung involvement after therapy, [5][6][7] so the ability to perform repeat treatments is essential. SBRT is limited in the number of lesions that can be treated due to accumulated toxicity to normal lung as well as cumulative skin and chest wall dose, while IGTA is repeatable with little impact on pulmonary function.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Immunological Aspects of NSCLC Cryoablation treatment option for unresectable primary and secondary peripheral lung tumors. [28][29][30][31][32][33] In percutaneous cryoablation, rigid cryotherapy probes are inserted with transthoracic computed tomography guidance and the target tumor becomes completely engulfed in an ice ball. 28,29 In patients with early-stage lung cancer who are not candidates for surgery because of comorbidities or poor lung function, percutaneous cryoablation of a primary tumor is potentially curative.…”
Section: May 2018mentioning
confidence: 99%